Combination of growth pattern and tumor regression identifies a high-risk group in neoadjuvant treated rectal cancer patients - Jeßberger, Jonas; Erlenbach-Wuensch, Katharina; Posselt, Rebecca; Haderlein, Marlen; Agaimy, Abbas; Fietkau, Rainer; Hartmann, Arndt; Distel, Luitpold (Journal of Digestive Diseases, 2017)
To analyze the prognostic effect of E-cadherin expression, the growth pattern of the tumor and the regression grade in a rectal cancer cohort treated with neoadjuvant radiochemotherapy (RCT).A total of 223 patients with rectal cancer treated with neoadjuvant RCT followed by surgery were included. Altogether 88 biopsies prior to RCT and 213 tumor resections in an average of 55 days post-RCT were investigated. Protein expression of E-cadherin and tumor growth pattern (solid glandular vs single-cell pattern) was assessed by staining tissue microarrays. The regression grade at the invasion front was determined according to the Dworak scale.There was a significant decrease of E-cadherin expression (P = 0.002) and a significant increased single-cell growth (P < 0.001) at the invasion front in tumor samples after RCT compared with primary biopsies of the tumor. A low E-cadherin expression in the biopsy was related to a longer metastasis-free survival (P = 0.033) and tumor-specific survival (P = 0.030). Post-RCT single-cell growth at the tumor invasion front was a prognostic factor for longer tumor-specific survival (P = 0.021). A combination of growth pattern and the Dworak regression grade was an independent prognostic parameter for tumor-specific survival (P = 0.015).Loss of E-cadherin protein expression in the pretreatment biopsy of rectal cancer is associated with fewer metastases and improved survival. Furthermore, the growth pattern in the post-RCT resection specimen has a prognostic value for survival. A combination of growth pattern and tumor regression score (the RegPat score) showed the highest discriminatory power to identify high-risk patients.
EVALuna2:6858

Regulatory T cells and cytotoxic T cells close to the epithelial–stromal interface are associated with a favorable prognosis - Rudolf, Julian; Büttner-Herold, Maike; Erlenbach-Wuensch, Katharina; Posselt, Rebecca; Jeßberger, Jonas; Haderlein, Marlen; Hecht, Markus; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (OncoImmunology, 2020)
Cytotoxic T cells and regulatory T cells play a crucial role in the outcome of cancer patients. Besides the density of these cells, it was shown recently that the spatial distribution is equally important. Here, we specifically analyzed the spatial distribution of these T cell subtypes at the epithelial–stromal interface in a rectal cancer cohort and its relevance for prognosis. We studied a cohort of 191 patients with advanced rectal cancer treated by radiochemotherapy (RCT). Tissue microarrays were immunohistochemical double-stained by FoxP3+ and CD+. Cell densities were analyzed in the stromal and epithelial compartment. Additionally, an image analysis software calculated the distances of lymphocytes to the epithelial–stromal interface (ESI). CD8+ and FoxP3+ cell counts decreased clearly after RCT with the decrease of FoxP3+ being more pronounced than of CD8+ cells. In the invasive front, short distances of the ESI to CD8+ and to FoxP3+ cells were associated with improved overall survival. Cell counts in the stromal compartment had no influence on prognosis. No correlation between stromal and epithelial lymphocyte densities was observed. The distance of epithelial–stromal interface to CD8+ and FoxP3+ cells was more accurate in predicting prognosis in the stromal compartment of rectal cancer patients than mere cell counts and could thereby be means of better stratifying patients for therapy. This observation will have to be validated in future prospective studies with regard to other tumor entities and its implications for the responsiveness of tumors to new therapeutic modalities.
CRIS-Team Scopus Importer:2020-04-28
Keywords: epithelial–stromal interface; rectal cancer; regulatory T cells; spatial distribution; ﻿cytotoxic T cells

Spatial distribution of FoxP3+ and CD8+ tumour infiltrating T cells reflects their functional activity - Posselt, Rebecca; Erlenbach-Wuensch, Katharina; Haas, Matthias; Jeßberger, Jonas; Buettner-Herold, Maike; Haderlein, Marlen; Hecht, Markus; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (Oncotarget, 2016)
Regulatory and cytotoxic T cells are key players in the host's anticancer immune response. We studied the spatial distribution of FoxP+ and CD8+ cells to identify potential interactions.In 202 patients 103 pre-radiochemotherapy biopsies and 153 post-radiochemotherapy tumour specimens of advanced rectal cancer were available and an immunohistochemical double staining of FoxP3+ and CD8+ tumour-infiltrating lymphocytes was performed to investigate cell density and cell-to-cell distances.FoxP3+ cells decreased after radiochemotherapy by a factor of 3 while CD8+ cells remained nearly unchanged. High epithelial (p=0.033) and stromal (p=0.009) FoxP3+ cell density was associated with an improved overall survival. Cell-to-cell distances of randomly distributed cells were simulated and compared to observed cell-to-cell distances. Observed distances shorter than the simulated, random distances were hypothesized to represent FoxP3+ cells actively interacting with CD8+ cells. Epithelial short distances were associated with a favourable prognosis while the opposite was true for the stromal compartment.The analysis of cell-to-cell distances may offer a tool to predict outcome, maybe by identifying functionally active, interacting infiltrating inflammatory cells in different tumour compartments.
EVALuna2:6815